Institutional Arrangements for Rural Poverty Reduction and Hunger Eradication in Uganda: An Empirical Analysis - Namara, Rose B.; Basheka, Benon C. (International Journal of Policy Studies, 2012)
Poverty reduction has been an overarching and universal goal for global and local development agendas. Global leaders chose to combine eradicating extreme poverty and hunger in the first Millennium Development Goal under the assumption that institutional arrangements to reduce poverty would automatically reduce hunger. Further assumptions suggested that all governments would design poverty reduction policies consistent with food security outcomes. We argue that concurrent hunger and poverty eradication in the rural settings of Uganda need direct institutional arrangements and action to reduce hunger as well as mechanisms that address other contextual factors. We empirically confirm that there are diverse determinants of hunger in Uganda with an associated socio-economic and political context. There is a relationship between poverty and hunger; therefore, government policies intended to address poverty need to embark on a synergy that coordinates interventions to address the interrelated societal problems of poverty and hunger.
Keywords: Poverty Reduction; Institutions; Hunger; Uganda